Psychosocial impact and self-esteem in patients seeking dental aesthetic treatment: a cross-sectional study using PIDAQ and RSES - Gumus Ayaz, Simge; Kececi, Gokce; Kokoz Citaker, Ozgun (Frontiers in Psychology, 2026)
BackgroundThe objective of our research is to find out how dental aesthetics affect people’s psychosocial status and self-esteem.Material and methodA total of 300 adult patients aged between 19 and 59 who presented to the Departments of Prosthetic Dentistry and Restorative Dentistry at Batman University Faculty of Dentistry for dental aesthetic treatment were included in this study. The Rosenberg Self-Esteem Scale (RSES) was used to measure self-esteem, while the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) was employed to assess psychosocial status. Subgroup comparisons were performed using the Tukey post-hoc test following one-way analysis of variance (ANOVA) for multiple group analyses. Differences between gender groups were assessed using the independent samples t-test. The relationship between self-esteem and psychosocial variables was analyzed using Pearson’s correlation analysis.ResultsNo statistically significant difference was found between genders in terms of total PIDAQ scores; however, women had significantly lower RSES scores compared to men. A statistically significant difference was observed in PIDAQ total scores based on educational level (p < 0.05), with university graduates scoring significantly lower than high school graduates. Additionally, a statistically significant but weak positive correlation was found between total PIDAQ scores and RSES scores (p < 0.05; r = 0.323), indicating that as psychosocial impact scores increased, self-esteem levels also increased.ConclusionThe demand for dental aesthetic treatment is significantly associated with individuals’ psychological wellbeing and self-esteem. Therefore, when planning restorative and prosthetic treatments, it is essential to consider not only functional aspects but also the physical, social, and psychological dimensions of dental aesthetics.